let n be Nat; :: thesis: for M1, M2, M3 being Matrix of n,REAL st M1 - M2 is_less_or_equal_with M3 holds

M1 - M3 is_less_or_equal_with M2

let M1, M2, M3 be Matrix of n,REAL; :: thesis: ( M1 - M2 is_less_or_equal_with M3 implies M1 - M3 is_less_or_equal_with M2 )

assume A1: M1 - M2 is_less_or_equal_with M3 ; :: thesis: M1 - M3 is_less_or_equal_with M2

A2: Indices M1 = [:(Seg n),(Seg n):] by MATRIX_0:24;

A3: ( len M1 = len M3 & width M1 = width M3 ) by Lm3;

A4: Indices (M1 - M2) = [:(Seg n),(Seg n):] by MATRIX_0:24;

A5: Indices (M1 - M3) = [:(Seg n),(Seg n):] by MATRIX_0:24;

A6: ( len M1 = len M2 & width M1 = width M2 ) by Lm3;

for i, j being Nat st [i,j] in Indices (M1 - M3) holds

(M1 - M3) * (i,j) <= M2 * (i,j)

M1 - M3 is_less_or_equal_with M2

let M1, M2, M3 be Matrix of n,REAL; :: thesis: ( M1 - M2 is_less_or_equal_with M3 implies M1 - M3 is_less_or_equal_with M2 )

assume A1: M1 - M2 is_less_or_equal_with M3 ; :: thesis: M1 - M3 is_less_or_equal_with M2

A2: Indices M1 = [:(Seg n),(Seg n):] by MATRIX_0:24;

A3: ( len M1 = len M3 & width M1 = width M3 ) by Lm3;

A4: Indices (M1 - M2) = [:(Seg n),(Seg n):] by MATRIX_0:24;

A5: Indices (M1 - M3) = [:(Seg n),(Seg n):] by MATRIX_0:24;

A6: ( len M1 = len M2 & width M1 = width M2 ) by Lm3;

for i, j being Nat st [i,j] in Indices (M1 - M3) holds

(M1 - M3) * (i,j) <= M2 * (i,j)

proof

hence
M1 - M3 is_less_or_equal_with M2
; :: thesis: verum
let i, j be Nat; :: thesis: ( [i,j] in Indices (M1 - M3) implies (M1 - M3) * (i,j) <= M2 * (i,j) )

assume A7: [i,j] in Indices (M1 - M3) ; :: thesis: (M1 - M3) * (i,j) <= M2 * (i,j)

then (M1 - M2) * (i,j) <= M3 * (i,j) by A1, A4, A5;

then (M1 * (i,j)) - (M2 * (i,j)) <= M3 * (i,j) by A2, A5, A6, A7, Th3;

then (M1 * (i,j)) - (M3 * (i,j)) <= M2 * (i,j) by XREAL_1:12;

hence (M1 - M3) * (i,j) <= M2 * (i,j) by A2, A5, A3, A7, Th3; :: thesis: verum

end;assume A7: [i,j] in Indices (M1 - M3) ; :: thesis: (M1 - M3) * (i,j) <= M2 * (i,j)

then (M1 - M2) * (i,j) <= M3 * (i,j) by A1, A4, A5;

then (M1 * (i,j)) - (M2 * (i,j)) <= M3 * (i,j) by A2, A5, A6, A7, Th3;

then (M1 * (i,j)) - (M3 * (i,j)) <= M2 * (i,j) by XREAL_1:12;

hence (M1 - M3) * (i,j) <= M2 * (i,j) by A2, A5, A3, A7, Th3; :: thesis: verum